A Study on Trends and Patterns of Cardiovascular Diseases in India Using Growth Models - Sujatha Inginshetty,; Anand B.,; Shweta S.,; M. Aasim,; Pavitra,; Suhasini, (International Journal of Scientific Research in Science and Technology, 2025)
Cardiovascular diseases (CVDs) are a major cause of death and an increasing public health concern in India. This study analyzed the trends and patterns of CVDs incidence and prevalence in India from 2000 to 2021 using exponential and logistic growth models. Data were obtained from the Global Burden of Disease study, and analyses were conducted separately for males and females. Both models effectively captured the increasing trends in CVDs, with high predictive accuracy. The logistic model generally performed better for males reflecting the possibility of stabilization in disease burden over time, while the exponential model was slightly better for females. The study highlights the importance of using gender-specific models for more accurate forecasting. These findings can support public health planning, resource allocation, and targeted interventions to manage the growing burden of CVDs in India.
Keywords: Cardiovascular diseases; Incidence; Prevalence; Exponential growth model; Logistic growth model